2006
DOI: 10.1038/sj.eye.6702515
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of day-case vitreoretinal surgery

Abstract: Purpose The indications for vitreoretinal (VR) surgery are increasing as equipment and techniques available improve. In order to decrease demand on limited health resources, day-case surgery would be beneficial in many cases. This study combines a retrospective and prospective arm to examine the feasibility and safety of routine day-case VR surgery. Methods One hundred consecutive patients (50 retrospective and 50 prospective) undergoing VR surgery within the Royal Berkshire NHS trust were included. The retros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 16 publications
(22 reference statements)
0
5
1
Order By: Relevance
“…The previously reported types and incidence of postoperative complications in patients who had undergone vitreoretinal surgery are summarized in Table 5 . The incidence of postoperative complications reported in our study were generally lower than those reportedly [ 5 25 ]. However, this study only analyzed cases where treatment plan changes were deemed necessary.…”
Section: Discussioncontrasting
confidence: 73%
“…The previously reported types and incidence of postoperative complications in patients who had undergone vitreoretinal surgery are summarized in Table 5 . The incidence of postoperative complications reported in our study were generally lower than those reportedly [ 5 25 ]. However, this study only analyzed cases where treatment plan changes were deemed necessary.…”
Section: Discussioncontrasting
confidence: 73%
“…A number of studies have shown the efficacy of local/sub-Tenon anesthesia for vitreoretinal procedures with respect to perioperative pain; however, there was often a need for the use of additional agents/sedatives (sub-Tenon or intravenous, respectively) by the attending anesthetist for more lengthy and complicated procedures such as repeat procedures and scleral buckling (6)(7)(8). There is evidence to show that local vs general anesthesia for vitreoretinal surgery does not influence the final anatomic/ visual outcome or intraoperative and postoperative complication rates (2,3) and that local/sub-Tenon anesthesia are well-tolerated by patients (1,5). Small-gauge vitrectomy has become increasingly popular in recent years, though its true benefits remain a subject of debate.…”
Section: Discussionmentioning
confidence: 99%
“…Unplanned readmission is an important indicator of the quality of care for ocular trauma patients. Several studies have surveyed the rate of unplanned readmission after AS . In a study on ambulatory sino‐nasal surgeries conducted in New York, Florida, Iowa, and California in 2010, 5% of the patients were found to revisit after surgery, of which 18.9% revisited the AS centre, 67% the emergency department, and 14.1% had inpatient admission .…”
Section: Introductionmentioning
confidence: 99%
“…However, no study has evaluated the unplanned readmission rate after ophthalmological AS. Existing studies on vitreoretinal AS are focused on postoperative pain or raised intraocular pressure (IOP), travelling distances, patient choice, and the demand of posturing after AS . Our study focused on the index of the 31‐day unplanned readmission rate, which reflects the occurrence of more severe cases postoperative complications.…”
Section: Introductionmentioning
confidence: 99%